Institutional Environment and Entrepreneurial Cognitions: A Comparative Business Systems Perspective - Lim, Dominic S.K.; Morse, Eric A.; Mitchell, Ronald K.; Seawright, Kristie K. (Entrepreneurship Theory and Practice, 2010)
In this study, we investigate the relationship between institutional elements of the social environment and entrepreneurial cognitions, which lead to the individual's venture creation decision. Employing a sample of 757 entrepreneurs and non–entrepreneurs from eight countries we examine the extent to which institutions influence venture creation decisions, where entrepreneurial expert scripts act as a mediator. Results show that various institutional elements, such as legal and financial systems, affect venture arrangements and willingness scripts. Venture arrangements scripts, in turn, have the most significant impact on an individual's venture creation decision.